Organisation and move structure in the results and discussion chapter in Malaysian undergraduates final-year projects - Mat Hussin, Nur Izyan Syamimi; Nimehchisalem, Vahid (Universiti Putra Malaysia Press, 2018)
Genre analysis studies on academic writing are mostly limited to analysis of articles. There is need for studies on undergraduate students' Final-Year Projects in the context of Malaysia. This study presents an analysis of 10 Final-Year Projects of English Language by final-year undergraduate students in a public university in Malaysia. Drawing on Yang and Allison's Moves and Steps model in the Results and Discussion sections, this study investigates the move structures used by the final-year undergraduates in their Results and Discussion chapters. The qualitative method was followed to collect and analyse the data. The data were collected purposively from Bachelor of Arts (English Language) students. The samples were analysed thematically by the researchers. Conclusions were drawn based on the rhetorical moves presented by the undergraduates in their Results and Discussion chapters. It was found that the moves most used were 'Reporting results' and 'Commenting on results'. The frequencies of both moves were higher compared with the frequency of 'Preparatory/Background information' and 'Summarising results'. The findings are expected to guide lecturers in designing instructional materials for teaching academic writing that focus on rhetorical structures and to raise students' consciousness of the structure of a well-written Results and Discussion chapter.